Transcholecystic approach for distal common bile duct stricture in a non-dilated biliary system: an alternative route. Issue 12 (29th December 2019) - Rahman, Syed; Krokidis, Miltiadis; Paraskevopoulos, Ioannis
Abstract : A 63-year-old patient was admitted to intensive treatment unit with biliary sepsis due to a small distal common bile duct stone. Endoscopic retrograde cholangiopancreatography was initially attempted for insertion of a biliary stent but failed due to the presence of a periampullary diverticulum. Referral to interventional radiology for percutaneous drainage was considered the next alternative even though there was no dilatation of intrahepatic ducts. Due to complete absence of intrahepatic duct dilatation, the traditional percutaneous transhepatic route was considered rather challenging. An alternative percutaneous approach via the gallbladder and subsequent catheterisation of the duodenum via the distal common bile duct was successfully performed instead without complication. We would like to describe this technique as an alternative option for drainage of the non-dilated biliary system in patients with sepsis.